Spillover of uncertainties of parallel markets on types of profit management with VAR-MGARCH approach - Adel Gardoon; Nader Khedri; Ali Mahmoodi; Mehdi Basert (تصمیم گیری و تحقیق در عملیات)
Purpose: Financial statements are the main decision-making bases of capital market actors, which are affected by internal and external factors. Uncertainty in other markets is one of the most important factors affecting the financial statements of listed companies. As a result, the current research aims to model the spillover of uncertainties of parallel markets on the types of profit management.Methodology: The present research is practical. The research period is a 10-year period with seasonal data between 2011 and 2021. The VAR-MGARCH model has been used to investigate the spillover of uncertainties of parallel markets on the types of profit management.Findings: Based on the results of the VECH, CCC, BEKK, and DCC models used to extract the uncertainty of the studied variables, the VECH models had higher accuracy. The spillover effect between different markets was observed based on the results of multivariate GARCH models. As a result, the uncertainty of one market strengthens the uncertainty between other markets. Based on the results of the vector autoregression model, the uncertainty of variables has a more substantial effect on accrual profit management than actual profit management. The variance analysis results show that oil price uncertainty has the highest contribution in the interpretation of real profit management change and exchange rate uncertainty in the interpretation of accrual profit management change.Originality/Value: Uncertainties of parallel markets reinforce each other and increase the level of profit management in the investigated companies.